New perspectives on angiotensin-converting enzyme 2 and its related diseases - Liu, Li-Ping (World J Diabetes, 2021)
Since the worldwide outbreak of coronavirus disease 2019, angiotensin-converting enzyme 2 (ACE2) has received widespread attention as the cell receptor of the severe acute respiratory syndrome coronavirus 2 virus. At the same time, as a key enzyme in the renin-angiotensin-system, ACE2 is considered to be an endogenous negative regulator of vasoconstriction, proliferation, fibrosis, and proinflammation caused by the ACE-angiotensin II-angiotensin type 1 receptor axis. ACE2 is now implicated as being closely connected to diabetes, cardiovascular, kidney, and lung diseases, and so on. This review covers the available information on the host factors regulating ACE2 and discusses its role in a variety of pathophysiological conditions in animal models and humans.